Estimation of Shockley–Read–Hall Lifetime in Homoepitaxial n‐GaN on Low‐Dislocation‐Density GaN Substrates Prepared by Hydride Vapor Phase Epitaxy and Maskless 3D. Issue 2 (27th July 2021) - Mochizuki, Kazuhiro; Ohta, Hiroshi; Horikiri, Fumimasa; Mishima, Tomoyoshi
Abstract : By eliminating the influence of surface recombination, the reported consideration that on‐resistance of GaN p + n diodes fabricated on free‐standing substrates should be limited by nonradiative recombination around dislocation lines is validated. The validation is based on analyses of 1) bulk nonradiative recombination current densities ( J nr ), determined from the y intercept of forward‐current density/inverse of anode radius plots, of diodes fabricated on two kinds of vapor‐phase epitaxially grown freestanding substrates (i.e., maskless 3D [M‐3D, dislocation density N dis  ≤ 4 × 10 5  cm −2 ] and void‐assisted separation [VAS, N dis  = 1–4 × 10 6  cm −2 ]) and 2) distributions of two‐photon photoluminescence (2PPL) from an n‐GaN layer identifying dislocations as dark spots. Based on the extracted values of J nr, the Shockley–Read–Hall lifetime of GaN p + n diodes on M‐3D and VAS substrates, τ SRH M‐ 3 D and τ SRH VAS are, respectively, estimated to be 11 and 2 ns. Under the assumption of high excitation for the 2PPL measurement, the use of τ SRH M‐ 3 D of 11 ns reproduces the 2PPL data with the effective dislocation radius ranging from 0.2 to 2 nm. Abstract : The reported limitation on the on‐resistance of GaN p + n diodes is mainly validated based on bulk nonradiative recombination current densities determined from the y intercept of forward‐current density/inverse of anode radius plots of diodes on maskless 3D (M‐3D; dislocation density N dis  ≤ 4 × 10 5  cm −2 ) and void‐assisted separation (VAS; N dis  = 1–4 × 10 6  cm −2 ) substrates.